Range finder measurement system using ultrasonic waves - Dhevindran, Ravi (2022)
The implementation of a distance measurement system utilizing ultrasonic waves is detailed in this project. The objective is to investigate and perform analysis to determine the appropriate optimization technique for the distance measurement. This paper includes simulation based study and research work using Proteus Professional 8 and Arduino IDE software. Results have been recorded and data analysis is performed in order to compare the performance of the simulation system.. The application of this project is the measurement of liquid level in tanks and obstacle sensing by using ultrasonic waves in Non-Destructive Test (NDT) system for oil and gas industries.